Impact of restorative treatment of tooth wear upon masticatory performance. (September 2019) - Kalaykova, Stanimira I.; Sterenborg, Bernadette A.M.M.; Loomans, Bas A.C.; Huysmans, Marie-Charlotte D.N.J.M.
Abstract: Objective: The restorative treatment of generalized tooth wear involves an increase in vertical dimension of occlusion and a comprehensive alteration of occlusal morphology. The aim of this study was to assess the impact of a direct adhesive restorative treatment on masticatory performance parameters. Materials and methods: A sample of 23 fully dentate adult generalized tooth wear patients (17 male, 6 female, age 41.7 ± 8.3 years) undergoing direct composite restorative treatment was selected. Before and one month after restorative treatment with resin bonded composite restorations, masticatory performance was evaluated using 1) a comminution test, 2) a maximum voluntary bite force recording and 3) the sum score of five items related to eating and chewing from the Oral Health Impact Profile (OHIP-49) questionnaire. Statistical analysis was performed using a paired t -test, and analysis per OHIP item was done by a McNemar test (p < 0.05). Results: There was no statistically significant difference in median particle size (X50) calculated before and after treatment (4.19 ± 0.97 and 4.03 ± 0.76, respectively, p = 0.327). Maximum voluntary bite force decreased significantly after treatment (baseline 389 ± 90 N, one month recall 323 ± 173 N, p = 0.028). The sum score of the five OHIP items significantly decreased after treatment (baseline 10.6 ± 4.8, one month recall 6.6 ± 2.5, p = 0.001), with the item regarding unsatisfactory diet showing the largest significance (p = 0.029). Conclusions: This study indicates that the restorative treatment of generalized tooth wear using direct resin bonded composite has no significant short-term effect on masticatory performance as measured with a comminution test, although the self-reported ability to eat and chew, as measured by the sum score of all pertaining OHIP items, did significantly improve. Clinical significance: On individual level, food comminution could be influenced by restorative treatment with increase of vertical dimension of occlusion, but at group level no significant effect is observed. Nevertheless, tooth wear patients do perceive improved ability to eat and chew foods, which is clinically relevant.